Comprehension Strategies as Cognitive Predictors of Multiteks Understanding: Evidence from a Mixed-Methods Study in Elementary Schools - Imelda Ratih Ayu; Arief Kuswidyanarko; Liza Murniviyanti; Puji Ayurachmawati; Fatikh Inayathur Rahma (Al-Qalam Institue, 2026)
The increasing use of written, audio, and audiovisual texts in 21st-century learning requires elementary students to employ effective comprehension strategies for processing multimodal information. This study examined students’ multiteks comprehension across different text modes and explored the potential predictive role of planning, monitoring, and evaluation strategies. An explanatory sequential mixed-methods design was employed involving 56 fifth-grade students from an elementary school in Palembang, Indonesia. Quantitative data were collected using a comprehension strategy questionnaire and a multiteks comprehension test, while qualitative data were obtained through open-ended questionnaires. Quantitative data were analyzed using descriptive statistics and Pearson correlation, whereas qualitative data were analyzed thematically. The results showed that students experienced the greatest difficulty with written texts (58.93% at the low level), while comprehension was higher for audio (82.1%) and audiovisual (89.3%) texts. Planning strategies showed significant positive correlations with comprehension across all text modes, whereas monitoring and evaluation strategies were associated with specific text modes. Qualitative findings indicated that high-achieving students applied comprehension strategies more systematically and metacognitively than low- and medium-achieving students. These findings suggest that comprehension strategies, particularly planning, may play an important role in supporting students’ multiteks understanding and should be explicitly integrated into elementary classroom instruction.